Astragaloside IV Inhibits NF-κB Activation and Inflammatory Gene Expression in LPS-Treated Mice - Wei-Jian Zhang; Balz Frei (Mediators of Inflammation)
In this study we investigated the role of astragaloside IV (AS-IV), one of the major active constituents purified from the Chinese medicinal herb Astragalus membranaceus, in LPS-induced acute inflammatory responses in mice in vivo and examined possible underlying mechanisms. Mice were assigned to four groups: vehicle-treated control animals; AS-IV-treated animals (10 mg/kg b.w. AS-IV daily i.p. injection for 6 days); LPS-treated animals; and AS-IV plus LPS-treated animals. We found that AS-IV treatment significantly inhibited LPS-induced increases in serum levels of MCP-1 and TNF by 82% and 49%, respectively. AS-IV also inhibited LPS-induced upregulation of inflammatory gene expression in different organs. Lung mRNA levels of cellular adhesion molecules, MCP-1, TNFα, IL-6, and TLR4 were significantly attenuated, and lung neutrophil infiltration and activation were strongly inhibited, as reflected by decreased myeloperoxidase content, when the mice were pretreated with AS-IV. Similar results were observed in heart, aorta, kidney, and liver. Furthermore, AS-IV significantly suppressed LPS-induced NF-κB and AP-1 DNA-binding activities in lung and heart. In conclusion, our data provide new in vivo evidence that AS-IV effectively inhibits LPS-induced acute inflammatory responses by modulating NF-κB and AP-1 signaling pathways. Our results suggest that AS-IV may be useful for the prevention or treatment of inflammatory diseases.